MAUSOLEUM AND TOMBSTONES OF THE OLD CEMETERY OF THE VILLAGE AGLOBI (TYPOLOGY, EPIGRAPHY, DECOR) - Zakariaev, Zamir Sahbanovic; Gasanov, Magomedrasid Anvarbekovic (History, Archeology and Ethnography of the Caucasus, 2021)
The article reviews the results of a comprehensive study of the previously unexamined tombstones of an old cemetery in the Dagestan village of Aglobi. The central spot of the cemetery is occupied by a large domical mausoleum with a burial inside it. In contrast with the majority of other Dagestan mausoleums, the structure in Aglobi is built of bricks. We believe that the mausoleum was originally built in the Late Middle Ages (15-16th centuries), which is indicated by the material used in constructing the building (thin elongated bricks). In the beginning of the 18th century it was renovated, which can be seen by the inscription dating 1114/1702-03. Presumably, the lining of its lower tier with decorative panels also dates back to the time of the renovation of the mausoleum. V.G. Kotovich’s dates the mausoleum 12-13th century, which we believe lacks justification. The study of the mausoleum’s epigraphy has allowed us to establish both the name of the buried, who was a Sufi (pir), and the name of the organizer of the renovation works. The latter is indicated by a social term mujavir, which has been recorded for the first time in Dagestan’s epigraphy. The analysis of the grave monuments demonstrates that the formation of the cemetery took place over several centuries. Apparently, the cemetery was originally formed around the unique mausoleum, since the oldest monuments are located near it. In general, the old tombstones of the cemetery chronologically cover the period from the Late Middle Ages to the middle of the 19th century. The study of the monuments includes an analysis of their typology (sarcophagi, rectangular-vertical steles), decorative elements. For the first time, the Arabic-language epigraphy of the Aglobi monuments is introduced into science. It was established that the style of the epitaphs, the external appearance and decorative design of the tombstones of the cemetery have direct analogies with the monuments of the Derbent zone, other historical regions of Southern Dagestan, and also Shirvan.
Keywords: Dagestan; Aglobi; cemetery; mausoleum; epigraphy; epitaphs; decor.